Cellular and molecular characterizations of the irregular internode division zone formation of a slow-growing bamboo variant. (11th October 2021) - Gao, Zhipeng; Guo, Lin; Ramakrishnan, Muthusamy; Xiang, Yu; Jiao, Chen; Jiang, Jiaweng; Vinod, Kunnummal K; Fei, Zhangjun; Que, Feng; Ding, Yulong; Yu, Fen; Chen, Tianguo; et al.
Abstract: The key molecular mechanisms underlying the sectionalized growth within bamboo or other grass internodes remain largely unknown. Here, we genetically and morphologically compared the culm and rhizome internode division zones (DZs) of a slow-growing bamboo variant ( sgv ) having dwarf internodes, with those of the corresponding wild type (WT). Histological analysis discovers that the sgv has an irregular internode DZ. However, the shoot apical meristems in height, width, outside shape, cell number and cell width of the sgv and the WT were all similar. The DZ irregularities first appeared post apical meristem development, in 1-mm sgv rhizome internodes. Thus, the sgv is a DZ irregularity bamboo variant, which has been first reported in bamboo according to our investigation. Transcriptome sequencing analysis finds that a number of cell wall biogenesis and cell division-related genes are dramatically downregulated in the sgv DZ. Interestingly, both transcriptomic and brassinosteroid (BR) contents detection, as well as quantitative real-time PCR analyses show that these irregularities have resulted from the BR signaling pathway defects. Brassinosteroid defect might also cause the erect leaves and branches as well as the irregular epidermis of the sgv . These results suggest that BR signaling pathway plays critical roles in bamboo internode DZ and leaf development from a mutant perspective and also explain the upstream mechanisms causing the dwarf internode of the sgv bamboo.